2014
DOI: 10.3354/meps10640
|View full text |Cite
|
Sign up to set email alerts
|

The first ‘lost year’ of Mediterranean sea turtles: dispersal patterns indicate subregional management units for conservation

Abstract: Identifying highly frequented areas is a priority for sea turtle conservation, and the distribution of young individuals in open waters represents a major knowledge gap due to methodological biases. The drift of hatchlings from 38 loggerhead Caretta caretta and 10 green Chelonia mydas turtle nesting sites in the Mediterranean was simulated for the first 6 mo of life, with simulations repeated for 5 different years (2001 through 2005). Results indicate that hatchlings from the Levantine and south-central Medite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 48 publications
9
50
0
Order By: Relevance
“…As with loggerheads, information on the distribution of small turtles is particularly deficient, but in green turtles this applies to larger juveniles as well, given that no tracking experiment has been ever undertaken. Hatchling dispersal simulations indicated that green turtle hatchlings are mainly retained in the Levantine basin, where the nesting sites are (Casale & Mariani 2014). A high proportion of green turtles smaller than 30 cm CCL was reported to occur in southern Turkey waters ) while low numbers of small turtles < 40 cm CCL frequent the Adriatic (Lazar et al 2004), especially in the southern part, the Ionian and even the Tyrrhenian seas around Italy (Bentivegna et al 2011).…”
Section: Green Turtlesmentioning
confidence: 99%
See 3 more Smart Citations
“…As with loggerheads, information on the distribution of small turtles is particularly deficient, but in green turtles this applies to larger juveniles as well, given that no tracking experiment has been ever undertaken. Hatchling dispersal simulations indicated that green turtle hatchlings are mainly retained in the Levantine basin, where the nesting sites are (Casale & Mariani 2014). A high proportion of green turtles smaller than 30 cm CCL was reported to occur in southern Turkey waters ) while low numbers of small turtles < 40 cm CCL frequent the Adriatic (Lazar et al 2004), especially in the southern part, the Ionian and even the Tyrrhenian seas around Italy (Bentivegna et al 2011).…”
Section: Green Turtlesmentioning
confidence: 99%
“…extension of shallow areas offering suitable neritic foraging sites is in the northern Adriatic and the Libyan/Tunisian shelf, these represent key areas for both Mediterranean green and loggerhead turtles, given that both areas are frequented by adults and juveniles. Other factors may, however, play a role in determining the movement patterns observed: for instance, recent evidence suggests that the foraging locations of adult turtles might be influenced by their drift scenarios as hatchlings Scott et al in press), and this would explain, for example, why few adults forage in the western part of Mediterranean, given that rookeries are confined to the Eastern basin (see also Casale & Mariani 2014). Mediterranean adult loggerheads do, however, exhibit some variety in their movements, with some turtles foraging in offshore oceanic waters for at least part of their inter-reproductive phase, sometimes keeping on the move without fixing to any specific site (Zbinden et al 2008;Luschi et al 2013;Schofield et al 2013).…”
Section: General Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The trajectories of passively drifting particles are compared with those of observed turtles released from the same date and nesting location in the western North Pacific, thereby testing the passive migration hypothesis for juvenile loggerhead sea turtles in the North Pacific Ocean. Such insights will help assess the role of long-distance transport from currents and provide useful long-term information on small juveniles during a period where little is known [40]. This knowledge can also provide critical geographical information for conservation management strategies in areas that may host high concentrations of young individuals from this population.…”
Section: Introductionmentioning
confidence: 99%